ANALISIS NILAI KALOR SECARA EKSPERIMENTAL DAN TEORITIK DARI BRIKET ARANG KULIT KEMIRI - Patabang, Daud (MEKTEK, 2009)
The aim of this article is to investigate heating value of candlenut shell Char briquette by experimental andtheoretical means. The experimental performs the High Heating Value HHV by Bomb Calorimeter PARR12611, and investigation in the theoretical ones by using Dulong’s formula.The result shows that the heating value of HHV is 10697,4 Btu/lbm, and by Dulong’s formula is10549,Btu/lb. There is 1,16% deviation of the two means because in the Dulong’s does not includedissociation effect